Philippines : Preparations for Inflation Targeting - Kongsamut, Piyabha (Washington, D.C. : International Monetary Fund, 2001)
The Philippines is planning to shift toward adoption of an inflation targeting framework in 2001. This paper reviews key policy issues in this context, describes various operational and technical preparations, and presents an empirical analysis of the factors driving inflation. Among the key policy requirements, while central bank independence appears assured, the exchange rate has been allowed to fluctuate largely freely, and the authorities are embarking on a medium-term plan for fiscal consolidation. Empirical results suggest that the effective exchange rate (rather than a bilateral rate) and wages are important long-run influences on inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet